Attitudes toward metabolic adverse events among patients with schizophrenia in Japan - Sugawara N (Dove Medical Press, 2016)
Norio Sugawara,1–3 Norio Yasui-Furukori,2,3 Manabu Yamazaki,4 Kazutaka Shimoda,3,5 Takao Mori,4 Takuro Sugai,3,6 Hiroshi Matsuda,4 Yutaro Suzuki,3,6 Yoshitake Minami,4 Yuji Ozeki,3,5 Kurefu Okamoto,4 Toyoaki Sagae,7 Toshiyuki Someya3,6 1Aomori Prefectural Center for Mental Health and Welfare, Aomori, 2Department of Neuropsychiatry, Hirosaki University School of Medicine, Hirosaki, 3Japanese Society of Clinical Neuropsychopharmacology, 4Japan Psychiatric Hospital Association, Tokyo, 5Department of Psychiatry, Dokkyo Medical University School of Medicine, Mibu, 6Department of Psychiatry, Niigata University Graduate School of Medical and Dental Sciences, Niigata, 7Department of Health and Nutrition, Yamagata Prefectural Yonezawa University of Nutrition Sciences, Yonezawa, Japan Background: Metabolic syndrome is a growing concern among patients with schizophrenia because metabolic abnormalities are widely regarded as a major risk factor for cardiovascular disease and premature death. The current study assessed attitudes toward metabolic adverse events among patients with schizophrenia. Methods: A brief questionnaire was constructed to investigate patient recognition of the following broad areas: dietary habits, lifestyle, self-monitoring, knowledge, and medical practice. Between January 2012 and June 2013, questionnaires were sent to patients associated with 520 outpatient facilities and 247 inpatient facilities belonging to the Japan Psychiatric Hospital Association. All of the participants (n=22,072; inpatients =15,170, outpatients =6,902) were diagnosed with schizophrenia based on the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, or the International Classification of Diseases, tenth revision. Results: Approximately 55.0% (8,069/14,669) of inpatients and 44.8% of outpatients (2,978/6,649) reported that they did not exercise at all. Although 60.9% (4,116/6,760) of outpatients reported that they felt obese, only 35.6% (5,261/14,794) of inpatients felt obese. More than half of the inpatients (51.2%; 7,514/14,690) and outpatients (60.8%; 4,086/6,721) hoped to receive regular blood tests to prevent weight gain and diseases such as diabetes. Conclusion: Although more than half of patients hoped to prevent weight gain and diabetes, only a minority of patients were mindful of eating balanced meals and having physical exercise. Educational efforts and the promotion of the best pharmacotherapy and monitoring practices are needed for patients with schizophrenia. Keywords: metabolic syndrome, schizophrenia, attitude, Japan